2011
DOI: 10.1111/j.2042-3292.2011.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal hyperammonaemia in a 35‐day‐old Warmblood‐cross filly

Abstract: Summary Hyperammonaemia of gastrointestinal origin has been an infrequently reported phenomenon in mature horses with abdominal disease. A large case study has previously been published describing the condition for the first time in both mature horses and foals. The case report below provides a detailed description of the treatment, clinical course and outcome of one of the foals in that report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Intestinal hyperammonaemia is an acquired condition that had, until 2011, only been reported in mature horses. The report by Unt et al (2012) in this issue, together with the case series from Dunkel et al (2011) highlights that the condition can indeed occur in foals and that perhaps we should be more vigilant for it.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Intestinal hyperammonaemia is an acquired condition that had, until 2011, only been reported in mature horses. The report by Unt et al (2012) in this issue, together with the case series from Dunkel et al (2011) highlights that the condition can indeed occur in foals and that perhaps we should be more vigilant for it.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore the second proposed mechanism of intestinal ammonium production, deamination of glutamine by phosphate-activated glutaminase located in villus enterocytes of the small intestine (Romero-Gomez et al 2009;Dunkel 2010), could be responsible for intestinal ammonia production in foals. That said, the case reported by Unt et al (2012) and 3 additional foals aged <1 month reported by Dunkel et al (2011) had a primary diagnosis of colitis or enterocolitis, suggesting that the large intestinal flora may have changed considerably. The further 3 young foals reported by Dunkel et al (2011) had a primary diagnosis of meconium impaction.…”
Section: Hyperammonaemia Of Intestinal Originmentioning
confidence: 99%
See 3 more Smart Citations